(untitled) (Research, Society and Development, 2023)
Introduction: Cannabis is the third most used psychoactive substance in the world. Its use, in addition to other comorbidities, has an impact on mental health, with emphasis on schizophrenic conditions, since around 26.6% of these patients suffer from Cannabis Use Disorder (CUD). The use of this drug is frequent in patients with psychotic disorders, such as schizophrenia, and it also seems to stimulate isolated psychotic conditions. The objective of the work is to elucidate the association between the use of cannabis and its impact on the establishment/progression of schizophrenia Methodology: This is an integrative review on the impact of cannabis use in the context of schizophrenia. Data from the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed) databases were used, by crossing the descriptors “Schizophrenia”, “Endocannabinoid system”, “Cannabis”, “THC” and “Cannabis psychosis”, to answer the question formulated through the PICO strategy. Results and discussion: The association between the two entities appears to be contained in a multifactorial genetic-behavioral relationship, in which early and exaggerated exposure to high concentrations of the drug, as well as family history and the polymorphism of some genes, appears to provide the individual with a condition of vulnerability to the earlier and more severe development of schizophrenia and/or psychotic events. Conclusion: The use of cannabis provides a more severe symptomatology, with early onset, with a high relapse rate, an early first hospital admission and recurrent psychotic conditions, this action being apparently provided by the interaction of THC with the endocannabinoid system.